The influence of exogenous recombinant HSP 70 on the alteration of membrane stiffness in hippocampal neurons following the modeling of neonatal hypoxic-ischemic injury in mice Authors - Vladimir M. Pokrovsky; Alexey V. Deikin; T Zhang; Nikolai A. Verlov; Andrey L. Konevega; Mikhail V. Korokin (Research Results in Pharmacology)
Introduction: The use of atomic force microscopy (AFM) to investigate membrane stiffness in neurons provides valuable insights into cellular mechanisms and their alterations in response to various pathophysiological conditions. Heat shock protein HSP 70, a component of the cellular stress response system, plays a role in stabilizing the protein structures of cellular organelles. However, studies examining changes in the stiffness of hippocampal neuronal membranes in its presence, particularly following cerebral circulation disturbances, have not been conducted yet.